Watershed management and gully erosion control are an approach for sustainable rural development; a case study of Qarnaq village in Golestan province - Saeedmohammad Sabouri (مسکن و محیط روستا)
Soil erosion in Iran is one of the major threats to rural settlements. Gully erosion plays a significant role in land degradation, particularly in semi-arid regions and soils with low cohesion. The purpose of this study is to investigate the effects of watershed management structures on the quality of life, prevention of rural migration, and satisfaction of rural residents with the implementation of these structures. Additionally, the study examines the performance of mechanical structures in controlling gully erosion and reducing vulnerability through library research, geology, geomorphology, and field observations of gullies and watershed management structures. Physical and environmental effects of implementing these structures are analyzed, and ultimately, a questionnaire is completed to assess the impact of watershed management structures on rural life in social, economic, physical, and environmental aspects. The study area is Qarnaq village in the mountainous region of eastern Golestan province, located in the sub-basin of Shoordeh in the Gorganrood river basin at coordinates 55.67° E and 37.71° N. Based on the conducted studies, the implementation of watershed management plans has had a significant impact on the social, economic, physical, and environmental aspects of the quality of life of rural residents. In addition to creating complete satisfaction with the implementation of watershed management structures, it has led to an increase in livestock and agricultural production, orchard development, and reverse migration to the village. The way in which these structures were implemented in Qarnaq village, through holding explanatory and educational classes for residents and beneficiaries, has increased the efficiency of the structures, improved the quality of life, and increased resident satisfaction. It is recommended that in rural settlements at risk of gully erosion, studies, implementation, and operation of watershed management plans be carried out through the participation of local residents.